INFLUENCE OF CaCl2 AND MILD HEAT TREATMENTS ON QUALITY OF READY-TO-EATJACKFRUIT DURING REFRIGERATED STORAGE - DARYANTI DARYANTI (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2005)
The objective of this research was to study of CaCl2 and mild heat treatments on quality of ready-to-eat Jackfruit during refrigerated storage. Ready-to-eat Jackfruits were dipped for 10 min in 1% solution of calcium chloride at 40 or 50Â°C. Firmness, concentration of bound-calcium, total soluble solid, acidity and sensory characteristics were evaluated during 13 days storage at 4Â°C. The result showed that the use of the treatments improved the keeping quality of ready-to-eat Jackfruit. The treated fruit showed higher value of ï¬rmness, concentration of bound-calcium, soluble solid content, acidity during storage and had better value on appearance, aroma, texture and acceptability than control